COMPARATIVE EFFICACY OF ACCEPTANCE AND COMMITMENT THERAPY (ACT) AND DIALECTIC BEHAVIOR THERAPY (DBT) IN REDUCING AGGRESSION IN PAKISTANI YOUNG ADULTS: A QUASI-EXPERIMENTAL STUDY - Abbas, Saima; Jegathevi Jegath, Anasuya (Malaysian Journal of Public Health Medicine, 2026)
Aggression is a serious issue with adverse consequences for individuals and society. Aggression among young adults has been an emerging psychological and social problem in Pakistan, which is worsened by socioeconomic stress, family and peer conflicts, poor impulse control, and lack of emotional regulation skills. Acceptance and commitment therapy (ACT) and Dialectical Behavior Therapy (DBT) are mindfulness-based therapies that have demonstrated potential in the management of aggression in the world. Nonetheless, their relative contributions in the Pakistani context remain underexplored. The current paper sought to draw parallels between the performance of ACT and DBT in the minimization of aggression and other associated mental consequences in young adults. A stratified random sampling technique was used to select a sample of 120 young adults, with a quasi-experimental pretest-posttest control group design (Acceptance and Commitment Therapy Experimental Group (ACT EG n = 40), Dialectical Behavior Therapy (DBT EG n = 40), and Control group n = 40). The groups will include males (n=20) and females (n=20). The Buss-Perry Aggression Questionnaire (BPAQ), the Positive Mental Health Scale, the Brief Psychiatric Rating Scale (BPRS), the World Health Organization Disability Assessment Schedule 2.0 (WHODAS 2.0), and the Depression Anxiety Stress Scales 21 (DASS-21) were used to test aggression, psychological symptoms, and functional impairments of the participants. The data was analyzed by using SPSS version 29 and Jamovi version 2.7.5. The results indicated a significant reduction in aggregate and individual aggression in the two intervention groups relative to the control group. The ACT group showed a greater decrease in overall aggression scores between pretest and the posttest (p <.001, Cohen's d=0.88) than the DBT group (p <.001, Cohen's d=0.64). Improvements were also observed in psychiatric symptoms and functional outcomes, with a large effect size observed in the ACT group. In conclusion, both Acceptance and Commitment Therapy and Dialectical Behavior Therapy were effective in reducing aggression among Pakistani young adults, with ACT demonstrating a comparatively more substantial effect. These findings support the use of evidence-based psychological Interventions for aggression management and emphasize the importance of early structured therapeutic approaches for young adult populations.